Analysis of Competency of Educators in Khoirul Ummah School Malang from The Perspective of Law Number 14 of 2005 about Teachers and Lecturers - Ahmadi Usman; Silviana Zahra (Didaktika Religia, 2020)
This study seeks to explain the competence of teaching staff/educators in Islamic education, the Khoirul Ummah School, Malang. The benchmark of change and strengthening teaching skills within the scope of Islamic educational institutions is using the competency analysis. The significance of the research lies in the analysis of the integration of modern science and the Islamic one. It used a descriptive qualitative survey research method with a documentary observation pattern and inquiry-based source tracking method. The findings reveal 1) aspects of personality competence, which characterized by moral and moral indicators, leadership and educational figures. In this competency, educators are highly qualified. The reason is that educators have a social competence enlightened by the kiai or cleric 2) aspects of professional competence. Here, family educators get a small scale. Educators master more the subject matter, compared to methods or learning concepts that are appropriate to the goals of the institution. In this aspect, 70% of educators do not understand concepts and methods, especially digital-based methods. 3) Aspects of social competence. In this aspect, educators become a good one if they can communicate and interact with students, guardians and surrounding communities. 60 % of educators are active in social activities and establish friendships with students’ guardians.